Characteristics of the schools resilient to violence. A study based on data from ICCS 2016 in Chile, Mexico and Colombia. (2021) - Arroyo Resino, Delia; Sandoval-Hernandez, Andres; Eryilmaz, Nurullah
Highlights: Results are based on data from IEA ICCS in Mexico, Colombia and Chile. Decision trees and cluster robust logistic regressions are used to analyse the data Students' attitudes are associated with schools' resilience to violence. Structured participation activities promote schools' resilience to violence. To a lesser extent, civic knowledge promotes school resilience to violence too. Abstract: Violence in schools is one of the main concerns in Latin American countries and is one of the main threats for schools to be effective in providing high-quality education. For this work, data from ICCS 2016 is used to fit decision trees and cluster robust logistic regression models to explore how some schools immersed in violent environments manage to be resilient to violence. Our results show that the variables most consistently associated with higher probabilities of a school being resilient to violence are those related to the students' attitudes and to a lesser extent, students' civic knowledge and family background. The paper concludes by discussing the possible policy and practice implications in the context of each of the countries analysed.